WARISAN MULAVARMMAN: MAKNA DAN KEBIJAKAN STRATEGIS - Kusmartono, Vida Pervaya Rusianti (Naditira Widya, 2008)
Every individual who has attended a 12-years-elementary education must be familiar with the lndic influenced name of "MOiavarmman", which marked the commencement of the historical era of the Indonesian Archipelago in early 4th Century. The written evidence of MOiavarmman's existence is inscribed on six of the seven yOpa of Muara Kaman. Besides the seven yOpa, archaeological traces of Hinduism are also discovered in settlement pouches along the Mahakam River Basin up to the upper river in the west and north. Nevertheless, the relationship among those material cultures is still a mystery; whether they can be identified as Oiavarmman's heritage is a question which needs further meticulous analysis for liable answers. Despite the present mystery, this article will discuss a glimpse of cultural occurrences in the eastern region of Kalimantan based on local narratives, the archaeological evidences of Hinduism on the Mahakam River Basin and their significance, and the strategic policy to accomplish the preservation-based benefiting from archaeological resources.